Application of B2C digital marketing - Simona-Valentina Pașcalau (Agora International Journal of Economical Sciences (AIJES), 2021)
The purpose of this paper is to understand the application of digital B2C marketing. Companies market directly to end customers or decision-makers through B2C marketing. Most B2C customers base their decisions on how they feel about a product or service, not on facts or how useful it is. B2C marketers can take advantage of this by developing customized content that appeals to the emotions of their target audience.
Keywords: 330